2002
DOI: 10.1164/rccm.200203-217oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-10 in the Intracellular Sequestration of Human Leukocyte Antigen-DR in Monocytes during Septic Shock

Abstract: Monocytes from many critically ill patients show a low level of major histocompatibility complex type II (MHC II) expression. This phenomenon is believed to play a role in these patients' increased susceptibility to secondary infections. In the present study, we show that the level of monocyte human leukocyte antigen (HLA)-DR expression inversely correlates with the degree of severity of the sepsis syndrome. The defect of the monocyte HLA-DR expression resides in an intracellular sequestration of the MHC II mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
4
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 56 publications
7
134
4
7
Order By: Relevance
“…Therefore, in adults and VLBW infants, the molecular mechanisms might also have similarities. Internalization of HLA-DR molecules could be one mechanism for the rapid HLA-DR decline (21). In adults, IL-10 reduced HLA-DR expression by inhibiting exocytosis and the recycling of existing HLA-DR (22).…”
Section: Immunodepression In Vlbw Infantsmentioning
confidence: 99%
“…Therefore, in adults and VLBW infants, the molecular mechanisms might also have similarities. Internalization of HLA-DR molecules could be one mechanism for the rapid HLA-DR decline (21). In adults, IL-10 reduced HLA-DR expression by inhibiting exocytosis and the recycling of existing HLA-DR (22).…”
Section: Immunodepression In Vlbw Infantsmentioning
confidence: 99%
“…Antiinflammatory cytokines such as IL-10, IL-4, IL-13, and TGF-β and non-cytokine mediators, including prostaglandin E 2 , catecholamines, and glucocorticoids, have been detected in the serum of patients and/or experimental animals with sepsis (38)(39)(40)(41)(42). In particular, IL-10 appears to contribute to sepsis-induced inhibition of macrophage responses (10,21,43). In our study, however, we found a trend toward increased IL-10 production in IRAK-M -/-animals following CLP and i.t.…”
Section: Figurementioning
confidence: 99%
“…Mechanistic data from human subjects with immunoparalysis are rare, but Fumeaux et al demonstrated internalization of cell-surface HLA-DR molecules in normal human monocytes upon co-incubation with serum from septic patients [49]. This monocyte deactivation was partially reversed by the addition of anti-IL-10 neutralizing antibodies.…”
Section: Mechanisms Of Immunoparalysismentioning
confidence: 99%
“…Numerous investigators have described reversal of endotoxin tolerance in vitro with agents including anti-IL-10 neutralizing antibody [49], IL-12 [67], GM-CSF [37,67,68], and flt3-ligand [69]. Hershman et al reported in 1989 that monocytes collected from immunoparalyzed adult trauma victims could be made to upregulate their HLA-DR expression upon ex vivo culture with the T H 1 cytokine IFNγ [70].…”
Section: Reversibility Of Immunoparalysismentioning
confidence: 99%